2010
DOI: 10.5047/eps.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the wind filtering effect of gravity waves observed at Allahabad (25.45°N, 81.85°E) in India

Abstract: Well-de ned coherent wave sources associated with the passage of short-period gravity waves were observed in all-sky images of OH emission on a total 21 occasions during January to May 2008 at Allahabad (25.45 • N, 81.85• E, dip lat ∼16.49• N) in India. The wave motions exhibited similar spatial and temporal properties during each month, but the north-east ward motions were distinctly dominant in April and May 2008. It is a wellknown theory that the upward propagating gravity waves may be blocked or absorbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…On the other hand, when many OLRs result in a few irregularities, the effectiveness of gravity wave seeding is in doubt. This could be due to the fact that the induced gravity wave generated in the ITCZ is blocked by the wind filtering effect around the mesospheric height in the upward propagation from the troposphere to the ionosphere (Mukherjee et al 2010) or by the polarization factor of the gravity wave that fails to trigger the irregularity occurrences (Tsunoda 2010b). Therefore, the current study concludes that the gravity wave induced in the convective clouds in the OLRs of ITCZ cannot be the sole seeding agent for the RT instability to produce irregularities year long at many longitude sectors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when many OLRs result in a few irregularities, the effectiveness of gravity wave seeding is in doubt. This could be due to the fact that the induced gravity wave generated in the ITCZ is blocked by the wind filtering effect around the mesospheric height in the upward propagation from the troposphere to the ionosphere (Mukherjee et al 2010) or by the polarization factor of the gravity wave that fails to trigger the irregularity occurrences (Tsunoda 2010b). Therefore, the current study concludes that the gravity wave induced in the convective clouds in the OLRs of ITCZ cannot be the sole seeding agent for the RT instability to produce irregularities year long at many longitude sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these systems provide a large field of view (FOV) using fisheye lenses (see e.g. Taylor et al, 1995;Shiokawa et al, 1999;Smith et al, 2009 andMukherjee et al, 2010). Others use a smaller aperture to focus on a distinct part of the night sky (e.g.…”
Section: P Hannawald Et Al: Fast Airglow Imagermentioning
confidence: 99%
“…Coordinated measurements of the nightglow features from the MLT region were carried out over Allahabad (25.5 • N, 81.9 • E) and Gadanki (13.5 • N, 79.2 • E), India under CAWSES India Phase II Programme during April 2009-May 2010 to study the propagation of gravity waves in the 13 • -27 • N latitude range. Earlier, Mukherjee et al (2010) studied the directional filtering effects of winds on the propagation of gravity waves over Allahabad using image data during February-May 2008, and found that the wave propagation was mostly directed towards the northeast direction. This preferential direction of gravity wave propagation towards the northeast is in line with the geometry of the two observing stations, with Gadanki located southwest of Allahabad.…”
Section: N Parihar and A Taori: An Investigation Of Long-distance Pmentioning
confidence: 99%
“…The imaging system (made by Keo Scientific Ltd., Canada) consisted of a 180 • field-of-view fish eye lens, telecentric optical system, 6-filter wheel assembly, re-imaging optical system, a backilluminated CCD sensor and the imager control system. The filter wheel assembly and CCD detector were thermoelectrically maintained at 25 and −53 • C, respectively (Mukherjee et al, 2010). Because of heavy contamination by city lights at low elevation angles, the field of view was reduced by a circular baffle.…”
Section: Imaging Observations At Allahabadmentioning
confidence: 99%